1991
DOI: 10.1007/bf00230374
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome b co-fractionates with gelatinase-containing granules in human neutrophils

Abstract: Subcellular fractionation studies in resting human neutrophils indicated a bimodal distribution for cytochrome b. A major peak of cytochrome b co-sedimented with gelatinase under different experimental conditions. This localization was partially overlapped with specific granules (using lysozyme and lactoferrin as specific granule markers), but clearly resolved from azurophilic granules, plasma membrane, mitochondria, as well as from a novel alkaline phosphatase-rich intracellular organelle. A minor localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 40 publications
1
48
0
Order By: Relevance
“…NADPH oxidase activation is therefore unlikely to involve crystalloid granules in eosinophils. This is in contrast to neutrophils, which express cytochrome b 558 in specific granules (48,49,53,59). The majority of NADPH oxidase activity in neutrophils undergoing arachidonate-or PMA-induced respiratory burst was found to localize to specific granules (58,60).…”
Section: Discussionmentioning
confidence: 89%
“…NADPH oxidase activation is therefore unlikely to involve crystalloid granules in eosinophils. This is in contrast to neutrophils, which express cytochrome b 558 in specific granules (48,49,53,59). The majority of NADPH oxidase activity in neutrophils undergoing arachidonate-or PMA-induced respiratory burst was found to localize to specific granules (58,60).…”
Section: Discussionmentioning
confidence: 89%
“…cytochrome b, required for superoxide anion generation, are mainly located in tertiary granules, with a secondary location in specific granules (6,7,9). Fusion of cytochrome b-rich granules with the plasma membrane is required for the production of reactive oxygen species (8,35).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, prevention of tertiary/specific granule fusion with phagosomes containing azurophilic granules may hamper the triggering of major anti-infection mechanisms. Likewise, lack of fusion of tertiary and specific granules, which harbor cytochrome b (6,8,9) responsible for the respiratory burst, with parasite-containing phagosome would prevent the triggering of the generation of oxygen metabolites highly toxic for the parasite. In fact, we found that L. major parasites did not trigger the respiratory burst in human neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…To prepare the distinct subcellular fractions, freshly prepared neutrophils (ϳ3-5 ϫ 10 8 ) were gently disrupted, and the postnuclear fractions were fractionated in 15-40% (w/w) continuous sucrose gradients as described previously (5,34). Subcellular fractions were analyzed for marker proteins for each organelle, namely lactate dehydrogenase (cytosol), HLA (plasma membrane), latent alkaline phosphatase (secretory vesicles), gelatinase (tertiary granules), lactoferrin (specific granules), and peroxidase (azurophilic granules) (34 -37).…”
Section: Subcellular Fractionationmentioning
confidence: 99%